Effect of antenatal dietary myo-inositol supplementation on the incidence of gestational diabetes mellitus and fetal outcome: protocol for a double-blind randomised controlled trial. Issue 1 (4th January 2022) - Ibrahim, Ibrahim; Abdullahi, Hala; Fagier, Yassin; Ortashi, Osman; Terrangera, Annalisa; Okunoye, Gbemisola
Abstract : Introduction: Gestational diabetes mellitus (GDM) affects 23.6% of Qatari women and is associated with maternal and perinatal morbidity and long-term risk of developing type 2 diabetes. A number of challenges exist with current interventions, including non-compliance with dietary advice, the reluctance of mothers to ingest metformin tablets or use insulin injections. These challenges highlight the importance of pursuing evidence-based prevention strategies. Myo-inositol is readily available as an US Food and Drug Administration-approved food supplement with emerging but limited evidence suggesting it may be beneficial in reducing the incidence of GDM. Further studies, such as this one, from different ethnic contexts and with differing risk factors, are urgently needed to assess myo-inositol effects on maternal and neonatal outcomes. Methods and analysis: This study is a prospective, randomised, double-blinded, placebo controlled clinical trial to either myo-inositol supplementation or placebo. We plan to enrol 640 pregnant women attending antenatal care at Sidra Medicine, Doha, Qatar, 320 in each arm. All participants will complete at least 12 weeks of supplementation prior to undertaking the Oral Glucose Tolerance Test at 24–28 weeks. The daily use of the trial supplementation will continue until the end of pregnancy. All outcome measures will be collected from the electronic medical records. Ethics and dissemination: Ethical approval for the study was obtained on 12 April 2021 from Sidra Medicine (IRB number 1538656). Results of the primary trial outcome and secondary endpoints will be submitted for publication in a peer-reviewed journal. Trial registration number: Prospectively registered on 26 May 2021. Registration number ISRCTN16448440 (ISRCTN registry).